The Relationship between Business Actors and Consumers According to the Review of Electronic Transaction Law - Muhammad Noor Ridani; Muhammad Syarif Hidayatullah; Fuad Luthfi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to analyze the relationship between business actors and consumers in electronic transactions according to a review of electronic transaction law in Indonesia. This research uses normative legal research methods with a doctrinal type of research. Primary data is obtained from primary legal materials such as laws, government regulations, and court decisions. Meanwhile, secondary data is obtained from secondary legal materials such as books, scientific journals and legal articles. The data analysis technique used is qualitative analysis. The research results show that the relationship between business actors and consumers in electronic transactions is regulated in Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), Law Number 8 of 1999 concerning Consumer Protection (UUPK), and statutory regulations. other related. Business actors have an obligation to provide correct and clear information about the products or services offered, as well as guarantee the security of electronic transactions. Consumers have the right to obtain correct and clear information about products or services, as well as the right to resolve disputes fairly.